Pengaruh Strategi Coping Terhadap Penyelesaian Tugas Pada Mahasiswa Prodi Bimbingan dan Konseling Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi - Siti Aisyah; Fadhilla Yusri; Afrinaldi; Junaidi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by a phenomenon that occurs in the field, namely several BK students from the class of 2022 who said that the very large number of coursework that must be submitted at every meeting and practical assignments that are also submitted simultaneously makes them feel pressured about the task. There are obstacles in completing the assignments that make these students lose motivation, so that students experience stress. This study aims to determine the effect of Coping Strategies on the completion of coursework for students of the BK study program class of 2022 UIN Sjech M. Djamil Djambek Bukittinggi. This study uses a quantitative correlational associative method. The population of this study was 154 students of the BK study program class of 2022. The sample was 46 students. The instrument used was a questionnaire. All instruments have met the requirements after being tested for validity and reliability. The data analysis technique used was a simple linear regression test. The results showed that the influence of coping strategies on task completion was 57.4%. The constant coefficient was 61.252. The regression coefficient of the emotion sub-variable was negative, meaning that every one-unit increase in emotion would decrease students' task completion by 0.213. Meanwhile, the regression coefficient of the problem sub-variable was positive, indicating that every one-unit increase in problem would increase students' task completion by 1.015.